Evaluation of Air Pollution Risk Factors from Polyurethane Plants, Workers Expose to Hexamethylene Diisocyanate (HDI) - M. Mirmohammadi; M. Hakimi; A. Ahamd; O. Kader; M. Mohammadian; S.B. Mirashrafi (Iranica Journal of Energy and Environment, 2010)
Isocyanates are known as highly reactive chemicals. Isocyanates/diisocyanates are often used as raw materials in production of polyurethane. The results of indoor air monitoring in all of the five polyurethane factories (n= 100) showed that all HDI concentration values were considered at high contaminated air, in comparison with exposure limit of 35μg/m3. The HDI concentration ranged from 62.24 to 92.7 μg/m3 with a mean HDI concentration of 78.8μg/m3. It was also shown that urinary HDA is detectable following HDI exposure. Urinary HDA concentration of the workers was found to be linearly related to HDI concentration of the air in the factories as correlated. The HDI work-related disease risk assessment of the present study showed that two personal and work condition variables were correlated with symptoms of HDI work-related disease in the polyurethane factories (workers’ weight and HDI pollution) (n= 350). A multiple linear regression analysis was performed to evaluate individual factors for developing asthma induced by diisocyanates. Two factors were statistically related to risk of work-related disease of diisocyanate at the 0.05 significance level. These were: (a) weight of exposed workers, (b) HDI pollution. None of them had experienced previous incidents of exposure to diisocyanates. This study has shown that air monitoring together with biological monitoring and also risk factors can be used to estimate the HDI pollution situation as well as the exposure to workers of polyurethane factories.